The Effect of Eight Weeks of Endurance Training on Positive and Negative Slopes on the Selected Biomechanical Parameters of the Femur Bone in Male Wistar Rats - Ravvaz, Azita; fatahi, Ali; Azarbayjani, Mohammad Ali ‬‬‬ (Journal of Clinical Physiotherapy Research, 2022)
Introduction: Regular exercise and physical activity is one way to promote health and prevent physical and mental diseases. This study aimed to investigate the effect of endurance training (ET) on positive and negative slopes (ETPS and ETNS, ±15°) on the biomechanical properties of the femur bone in male Wistar rats. Materials and Methods: This experimental study was performed on 15 male Wistar rats with an approximate age of eight weeks and a weight range of 180-200 g. For this purpose, the rats were divided into three groups, namely, the control (without activity), ETPS, and ETNS groups. The ET program was performed five days a week for eight weeks. The obtained data were statistically analyzed using the one-way ANOVA test at P<0.05. Results: Significant improvement was observed in biomechanical variables including maximum force, strength, deformation, and maximum absorbed energy of the femur bone in the ETPS group compared with the other two groups. However, the ETNS reduced all biomechanical variables of the femur bone. Conclusion: The results indicated that ETPS is effective in improving bone indices. Given the significant difference between the ETPS and ETNS groups in the biomechanical parameters of the bone, it is suggested that a training program with different intensity and duration levels be implemented in other age groups on different slopes.